1996
DOI: 10.1080/095008396180812
|View full text |Cite
|
Sign up to set email alerts
|

Superheating and melting-point depression of Pb nanoparticles embedded in Al matrices

Abstract: Two kinds of Pb± Al granular sample (with nanometre-sized Pb particles embedded in an Al matrix) were prepared by using melt-spinning and ballmilling techniques. The Pb particles were synthesized with similar particle sizes, about 5± 30nm in diameter, but were observed to have different Pb± Al interfaces for samples prepared using different approaches. In the melt-spun Pb± Al samples, the Pb nanoparticles were seen to have an epitaxial relationship with the Al matrix, while the Pb particles in the ball-milled … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
39
2

Year Published

2004
2004
2021
2021

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 136 publications
(49 citation statements)
references
References 4 publications
6
39
2
Order By: Relevance
“…They were later verified by Goswami and Chattopadhyay (1997) and Johnson and his collaborators (Grå baek et al, 1992;Johnson et al, 1990; for further details see also Andersen and Johnson, 1995, and references therein). The results have also been confirmed by Sheng and his collaborators in Shenyang (Sheng et al, 1996(Sheng et al, , 1998 who also noted that lead inclusions in ball milled aluminum-lead alloys often had random orientations and, subsequently, loss of distinct facets. This group also invented a process for making alloys with high lead concentrations by the use of consecutive rolling and folding of multilayer lead aluminum sandwiches that eventually would introduce break-up of the layers into a nanostructured material .…”
Section: Solid Noble Gas Inclusionssupporting
confidence: 79%
See 2 more Smart Citations
“…They were later verified by Goswami and Chattopadhyay (1997) and Johnson and his collaborators (Grå baek et al, 1992;Johnson et al, 1990; for further details see also Andersen and Johnson, 1995, and references therein). The results have also been confirmed by Sheng and his collaborators in Shenyang (Sheng et al, 1996(Sheng et al, , 1998 who also noted that lead inclusions in ball milled aluminum-lead alloys often had random orientations and, subsequently, loss of distinct facets. This group also invented a process for making alloys with high lead concentrations by the use of consecutive rolling and folding of multilayer lead aluminum sandwiches that eventually would introduce break-up of the layers into a nanostructured material .…”
Section: Solid Noble Gas Inclusionssupporting
confidence: 79%
“…Melting was found to be curvature driven with a melting point depression that was largest for the inclusions with the smallest radius of curvature (Kofman et al, 1994;Lereah et al, 2001). The discrepancy between observations of superheating effects and premelting effects was solved in 1996 when Sheng and collaborators (Sheng et al, 1996) presented evidence for the assumption that superheating of the lead inclusions in aluminum was associated with the low energy of the interface facets. Using in-situ TEM analysis, they showed that faceted and aligned lead inclusions in rapidly solidified alloys melted significantly above the bulk melting point of lead, while similar inclusions in ball milled alloys without preferred orientation and without low-energy facets melted below the bulk melting point, e.g., under conditions where ␥ sm Ͼ ␥ lm .…”
Section: Melting and Solidification Of Lead Inclusionsmentioning
confidence: 94%
See 1 more Smart Citation
“…An MD calculation suggested that a 115 K overheating occurs to Pb(111) films confined in an Al(111) matrix [262]. The T m suppression for a free surface is attributed to the reduced degree of confinement, and hence the increased entropy of the molecules at the surface compared with atoms in the bulk, whereas the T m elevation or depression of the embedded nanosolids depends on the coherency between the nanosolids and the embedding matrix [263,264].…”
Section: Outstanding Modelsmentioning
confidence: 99%
“…However, for the embedded NPs the melting point is not only related to NPs' size, structure and shape; but also affected by the embedding matrix. For some matrices, melting of the embedded NPs occurs in lower temperature than its bulk state, while it is possible for the same NPs to have superheating above the melting point in some other matrices [31][32][33][34][35]. Qi et al [36] have developed a new model to accounting for the size and shape dependent superheating of nanoparticles embedded in a matrix where the particle shape is considered by introducing a shape factor.…”
Section: Structural Characterizationmentioning
confidence: 99%